HSP90 is part of a protein complex with the L polymerase of Rift Valley fever phlebovirus and prevents its degradation by the proteasome during the viral genome replication/transcription stage - Alem, Farhang; Brahms, Ashwini; Tarasaki, Kaori; Omole, Samson; Kehn-Hall, Kylene; Schmaljohn, Connie S.; Bavari, Sina; Makino, Shinji; Hakami, Ramin M. (Frontiers in Cellular and Infection Microbiology, 2024)
The mosquito-borne Rift Valley fever virus (RVFV) from the Phenuiviridae family is a single-stranded RNA virus that causes the re-emerging zoonotic disease Rift Valley fever (RVF). Classified as a Category A agent by the NIH, RVFV infection can cause debilitating disease or death in humans and lead to devastating economic impacts by causing abortion storms in pregnant cattle. In a previous study, we showed that the host chaperone protein HSP90 is an RVFV-associated host factor that plays a critical role post viral entry, during the active phase of viral genome replication/transcription. In this study, we have elucidated the molecular mechanisms behind the regulatory effect of HSP90 during infection with RVFV. Our results demonstrate that during the early infection phase, host HSP90 associates with the viral RNA-dependent RNA polymerase (L protein) and prevents its degradation through the proteasome, resulting in increased viral replication.